Acupuncture Management of Post-Term Pregnancy with Spleen Qi Deficiency to Promote Uterine Contractions: A Case Study - I Gusti Ayu Suprapti; Chantika Mahadini; Puspo Wardoyo; Ikhwan Abdullah (International Journal of Health and Pharmaceutical (IJHP), 2026)
Prolonged labor caused by weak uterine contraction is conventionally managed with synthetic oxytocin, which carries potential adverse effects. In Traditional Chinese Medicine, weak uterine contraction is frequently associated with Spleen Qi Deficiency, presenting as physical exhaustion, edema, and inadequate energy for childbirth. This study aims to evaluate the efficacy of acupuncture as a non-pharmacological intervention to stimulate uterine contraction in a postterm pregnant woman experiencing Spleen Qi Deficiency. A clinical case study was conducted at Klinik Bumi Sehat Ubud, Bali, involving a 40-week pregnant participant who exhibited an initial absence of uterine contraction, lower limb edema, severe fatigue, and a weak pulse. The therapeutic intervention consisted of six consecutive acupuncture sessions utilizing specific acupoints, including Sanyinjiao (SP6), Zusanli (ST36), Hegu (LI4), and Yinlingquan (SP9), combined with moxibustion, to eliminate damp-cold pathogens, regulate Qi, and tonify the spleen. The results demonstrated a progressive and significant clinical improvement; the participant's lower limb edema resolved entirely, and maternal physical stamina was fully restored. Furthermore, active and strong uterine contraction was successfully induced, culminating in a normal and spontaneous vaginal delivery. In conclusion, targeted acupuncture therapy serves as a highly effective and safe holistic approach for addressing delayed labor and maternal fatigue attributed to Spleen Qi Deficiency, thereby offering a viable complementary intervention in obstetric care.